Konsep Model Formulasi Rasio Kebutuhan Bahan Perpustakaan (Analisis Kuantitatif Kebutuhan Bahan Perpustakaan Sekolah Tinggi Agama Islam Negeri Curup Tahun 2017) - Misroni Misroni; Rahmat Iswanto (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This article is a concept that aims to answer some problems. They are what factors determine the library users’ needs, how to formulate the ratio of the needs, how the formulation of the ratio of the needs for users of the State Islamic University of Curup and how the collection deviates from the needs. The type of this research is descriptive analysis research. The population of this research is the civitas academic of State Islamic University of Curup in 2017. The process of analysis is done by laying down descriptive concepts so that it could create a formula that can be used to measure the needs of library materials. The minimum amount of library material for the State Islamic University of Curup is 38,516 titles. The deviation occur because of collections damage, collection losses, out-of-date collections, the addition of the number of users, the development of university, and the lending to college employees who are not counted as library’s users.The Library of the State Islamic University of Curup still need to communicate well to its users so that what they need can be recorded and fulfilled by the library.